Development and Application of UAV VR Panoramic Display System for Datengxia Water Project - ZHANG Yao; HUANG Pengjia; ZHU Changfu (Renmin Zhujiang)
With the rapid development of computer network technology,panoramic technology has been widely applied in many fields such as tourism,real estate,engineering construction,and virtual education.It realizes the all-round interactive viewing and browsing in real scenes,with the sense of the scene and interaction.This paper obtains the panoramic images by the UAV aerial photography and image stitching technology,develops the UAV VR panoramic display system of Datengxia Water Project based on krpano engine and geographic information technology for realizing many functions including panoramic data storage management,online editing,releasing,etc.After the system is applied to the panoramic data management of Datengxia,there are lots of good feedback,and the work efficiency is greatly improved.In addition,this panoramic system provides data support for the virtual monitoring of the Datengxia Water Project construction,promotes the classification and efficient retrieval of panoramic data in the project,improves the efficiency of users in making panoramic projects and managing panoramic data,and offers an operation platform for building the Datengxia Water Project exhibition site and the VR display project of the Datengxia Museum.